Research on 3D Magnetic Memory Signals Induced by Circular Hole Defects - Bin Yang; Zhifeng Liu; Yang Gao (Magnetochemistry, 2025)
Metal magnetic memory testing technology can not only detect macroscopic defects in ferromagnetic materials but also rapidly and conveniently detect early damage and stress concentration areas of components. Therefore, it is widely used in the nondestructive testing of ferromagnetic materials. However, the mechanism of magnetic memory detection is not yet clarified, and experimental research is unsystematic. Previous studies mainly focus on the normal and tangential components of magnetic memory signals (MMSs), and the third directional component is rarely considered, resulting in problems such as missed detection and misjudgement in practical applications. In this research, specimens without and with a circular hole defect were designed, and the correlation between the 3D MMS and the defect size, as well as the applied load, were investigated using tensile tests. Magnetic parameters were defined to characterize the stress and defect-induced abnormal magnetic change. The effects of applied load and defect size on magnetic parameters were discussed. The experimental results showed that the peak–valley difference in the 3D MMS increases with increasing load and defect size, and the peak–valley spacing in the 3D MMS is not influenced by applied load but increases with increasing defect size. The 3D MMS gradient exhibits a good correlation with the equivalent stress along the loading direction. Additionally, the applied load and defect size were quantitatively evaluated by utilizing the Lissajous figure area generated from the X and Z components of the 3D MMS. Finally, a nonlinear fitting equation for defect size evaluation was presented. This study can provide a theoretical basis for the quantitative detection and evaluation of defect size and stress in engineering applications.